Jaminan Kepastian Keberlangsungan Hegemoni Amerika Serikat di Indonesia pada Era Pemerintahan Joe Biden - Smithiana, Meidia (Indonesian Journal for Social Responsibility, 2022)
'Americanization' is a term that refers to anything that has an American element to it. Americanization penetrated into Indonesia through politics, economics, and so on. Therefore, this study aims to see how the influence of the United States in Indonesia in the Joe Biden era, both positive and negative impacts. This study uses the theoretical approach of hegemony and post-hegemony. Data were taken from related articles and analysed using the method of recording important information from articles. The results of this study find that the United States is still influential in Indonesia in all fields through the power of software to this day in accordance with the post-hegemony theory which underlines the formation of a continuous system of hegemony.